2017
DOI: 10.7554/elife.31476
|View full text |Cite
|
Sign up to set email alerts
|

Yeast eIF4A enhances recruitment of mRNAs regardless of their structural complexity

Abstract: eIF4A is a DEAD-box RNA-dependent ATPase thought to unwind RNA secondary structure in the 5'-untranslated regions (UTRs) of mRNAs to promote their recruitment to the eukaryotic translation pre-initiation complex (PIC). We show that eIF4A's ATPase activity is markedly stimulated in the presence of the PIC, independently of eIF4E•eIF4G, but dependent on subunits i and g of the heteromeric eIF3 complex. Surprisingly, eIF4A accelerated the rate of recruitment of all mRNAs tested, regardless of their degree of stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
120
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(144 citation statements)
references
References 93 publications
(176 reference statements)
23
120
1
Order By: Relevance
“…The current model is that the 5 ′ end will be bound by either nuclear cap-binding complex or eIF4F, and this will recruit eIF4A or Ded1/DDX3, which would then unwind the 5 ′ UTR. An alternative view is that the role of eIF4A is to extract the 5 ′ end of the mRNA from the overall mRNA structure, thereby allowing for assembly of Ded1/Ddx3 and cis unwinding of the 5 ′ UTR to allow MFC loading (Yourik et al 2017). In contrast, since the 3 ′ -UTR is more structured that the coding region (in zebrafish, fruit flies, worm, and humans) (Li et al 2012;Wan et al 2014;Beaudoin et al 2018), RNA structures in the 3 ′ UTR may help terminate translation by stalling ribosomes at the stop codon.…”
Section: Entry and Exit Of Translationmentioning
confidence: 99%
“…The current model is that the 5 ′ end will be bound by either nuclear cap-binding complex or eIF4F, and this will recruit eIF4A or Ded1/DDX3, which would then unwind the 5 ′ UTR. An alternative view is that the role of eIF4A is to extract the 5 ′ end of the mRNA from the overall mRNA structure, thereby allowing for assembly of Ded1/Ddx3 and cis unwinding of the 5 ′ UTR to allow MFC loading (Yourik et al 2017). In contrast, since the 3 ′ -UTR is more structured that the coding region (in zebrafish, fruit flies, worm, and humans) (Li et al 2012;Wan et al 2014;Beaudoin et al 2018), RNA structures in the 3 ′ UTR may help terminate translation by stalling ribosomes at the stop codon.…”
Section: Entry and Exit Of Translationmentioning
confidence: 99%
“…We also found that the HLH mutation destabilizes interactions of initiation complexes with EIF4A1 in a transcript-specific manner, possibly due to weakening eIF3 binding to pre-initiation complexes ( Fig. 2) (31). The interaction of the HLH motif in EIF3A and EIF4A1 with the mRNA at the exit and entry points of the initiation complex, respectively, likely affects the dynamics of mRNA scanning to the start codon in a transcript-specific manner, as well as affecting mRNA recruitment (22,31).…”
Section: Discussionmentioning
confidence: 66%
“…2) (31). The interaction of the HLH motif in EIF3A and EIF4A1 with the mRNA at the exit and entry points of the initiation complex, respectively, likely affects the dynamics of mRNA scanning to the start codon in a transcript-specific manner, as well as affecting mRNA recruitment (22,31). This transcript specificity is enhanced in the presence of RocA, which locks EIF4A1 onto poly-purine stretches in the 5'-UTR, thereby stalling scanning and mRNA unwinding (18).…”
Section: Discussionmentioning
confidence: 99%
“…Since mRNAs with long and highly structured 5'UTRs are proposed to depend strongly on eIF4A-mediated unwinding (Svitkin et al, 2001;Waldron et al, 2018;Wolfe et al, 2014), it is at first glance surprising that among the 1000 mRNAs with significantly reduced translational efficiency were also mRNAs of ribosomal proteins with predominantly short and unstructured 5'TOP motifs (Table S1). However, Lorsch and colleagues recently showed that eIF4A enhances translation of mRNAs regardless of their structural complexity in yeast (Yourik et al, 2017) and inhibiting eIF4A with hippuristanol or mTOR with PP242 represses a subset of common mRNAs including most ribosomal mRNAs (Iwasaki et al, 2016). Hence, it is conceivable that structural perturbation of the eIF4F complex affects several mRNAs including the highly-translated ribosomal mRNAs.…”
Section: Discussionmentioning
confidence: 99%